Magnetic layer thickness dependence of all-optical magnetization switching in GdFeCo thin films. (20th June 2016) - Yoshikawa, Hiroki; El Moussaoui, Souliman; Terashita, Shinnosuke; Ueda, Ryohei; Tsukamoto, Arata
Abstract: To clarify the relationship between all-optical magnetization switching (AOS) and nonlocal and nonadiabatic energy dissipation process, we focus on the contribution from energy dissipation in the depth direction. Differently designed structure dependence of created magnetic domain is observed from the reversal phenomenon, AOS, or multidomains by thermomagnetic nucleation (TMN) in GdFeCo multilayer thin films. TMN depends on the shared absorbed energy throughout the continuous metallic volume. On the other hand, AOS critically depends on nonadiabatic energy dissipation process with the electron system in sub-picoseconds. Furthermore, the laser fluence dependence of AOS-created domain sizes indicates that the value of irradiated laser fluence threshold per magnetic domain volume is almost constant. However, a lower laser irradiation fluence below 1–2 mW has a larger value and thickness dependence. From these results, we suggest that AOS depends on energy dissipation from the incident surface in the depth direction for a few picoseconds.